Characterization of Inter- and Intramolecular Interactions of Amyloid Fibrils by AFM-Based Single-Molecule Force Spectroscopy. (7th August 2016) - Li, Yinli; Liang, Hao; Zhao, Huiling; Chen, Dong; Liu, Bo; Fuhs, Thomas; Dong, Mingdong
Abstract : Amyloids are fibrous protein aggregates defined by shared specific structural features. Abnormal accumulation of amyloid in organs leads to amyloidosis, which results in various neurodegenerative diseases. Atomic force microscopy (AFM) has proven to be an excellent tool investigating amyloids; it has been extensively utilized to characterize its morphology, assembly process, and mechanical properties. This review summarizes studies which applied AFM to detect the inter- and intramolecular interactions of amyloid fibrils and classified the influencing factors of amyloid's nanomechanics in detail. The characteristics of amyloid fibrils driven by inter- and intramolecular interactions, including various morphologies of amyloid fibrils, self-assembly process, and the aggregating pathway, are described. Successful examples where AFM provided abundant information about inter- and intramolecular interactions of amyloid fibrils in different environments are presented. Direct force measurement of intra- or intermolecular interactions utilizing an AFM-based tool, single-molecular force spectroscopy (SMFS), is introduced. Some mechanical information such as elasticity, adhesiveness, and strength was obtained by stretching amyloid fibrils. This review helps researchers in understanding the mechanism of amyloidogenesis and exploring the properties of amyloid using AFM techniques.